Observability analysis and robust observer design for a continuous yeast culture. (August 2021) - Jerono, Pascal; Schaum, Alexander; Meurer, Thomas
Abstract: The observer design problem for state estimation in a continuous (or semi-continuous) yeast fermentation using Sonnleitner's bottleneck model is addressed. The system's detectability and partial observability properties are rigorously established and an observer for on-line state reconstruction is designed as a combination of a geometric and a reduced order asymptotic observer which robustly converges in the sense of input-to-state stability. The performance of the observer is evaluated with numerical simulations and experimental data from a continuous yeast fermentation in a 2 l lab-scale reactor. Highlights: Detectability and observability of a continuous yeast fermentation model are analyzed. A geometric reduced order observer is proposed. Robust convergence in the sense of input-to-state stability is established. Experimental and numerical validations are presented.